Isomerisasi Linoleat dalam Minyak Jarak Hasil Dehidrasi Menjadi Linoleat Terkonjugasi dan Pemisahannya dengan Kromatografi Kolom Fasa Diam Silika Gel yang Diimpregnasi Perak Nitrat - Marham Sitorus; Sanusi Ibrahim; Hazli Nurdin; Djaswir Darwis (Institut Teknologi Bandung, 2011)
The main component of dehydrated castor oil (DCO) is linoleic and conjugated linoleic acid (CLA) as triglyseride forms. This research aim is to find out suitable method for linoleic isomerization of DCO into CLA. Isomerization method must be made chemoselective in order to prevent safonification and transesterification. Isomerization method with 2M NaOH in n-butanol, 1% KOH (w/v) without solvent and irradiated by microwave with iodine as an initiator were tested respectively. CLA was seperated by using column chromatography that AgNO3 impregnated silica gel as a stationary phase. Seperation was based on the differences of coordination bond strenght between the double bond and silver ion. Its the more unsaturation and trans isomer the more srongly the molecule is retained. Gradient elution was carried out by various ratio of hexane and acetone (v/v) e. g : 97.5 : 2.5, 95 : 5, 90 : 10, 80 : 20, 70 : 30 and 60: 40 with 8 x 5 mL. Each of fraction was analyzed by using TLC and the spot detection was made by UV lamp. The results was analyzed by using GC, FTIR, UV and GC - MS and Its compared with the standard data. The best isomerization was conducted by microwave irradiated using iodine as an initiator with a conversion factor of 1.97 %. Seperation of CLA could be made by column chromatography that AgNO3 impregnated silica gel as a stationary phase. The best result was conducted by eluting with 95: 5 (v/v) of hexane-acetone. The compositions of seperated were: 0,91% (9c-2c) linoleic, 43.59% (9c/t-12t/c) linoleic, 18.58% (9c/t-1t/c)CLA, 3.46% (9t-11t) linoleic, 19.19%(9t- 1t) CLA and 0.86% ricinoleic. The ratio of CLA : linoleic prepared was 0.77 : 1 or 70, 32 % compared to the standar with the proportions of 1.45:1.